Trans-diagnostic and trans-theoretical therapy for personality disorder - Livesley, W. John (Revista de Psicoterapia, 2018)
This paper argues that evidence of limited efficacy of specialized therapies for personality disorder points to the need for trans-diagnostic and trans-theoretical treatment models. Current therapies largely adopt a diagnosis-specific and therapeutic schools approach to therapy development; each major school of thought tends to develop its own treatment model for specific diagnoses. The relevance of a diagnosis specific approach to treatment is challenged given the well-established problems with current diagnoses and growing recognition that the general features of personality disorder and severity are more useful in understanding prognosis than specific diagnoses. These developments point to the use of a trans-diagnostic treatment model. Similarly, a schools approach to treatment is questioned given the failure to demonstrate differences in efficacy across therapeutic models and evidence that these therapies do not yield better outcomes that supportive therapy or general clinical care. These finding point to the need for a more integrated approach. Implementation of trans-diagnostic and trans-theoretical treatment requires a more detailed assessment of personality pathology than is provided by current diagnoses in order to identify impairments that form the targets for change and a scheme for organizing therapy and coordinating the implementation of an eclectic array of interventions. The article outlines a practical way to conceptualize assessment for treatment purposes and a framework for organising and delivering therapy.